AI-Powered Cryptocurrencies and Sustainability: The Role of Intelligent Blockchains in Green Technology Development - Kovács, Imre Mátyás; Fűrész, Ágnes; Szeberényi, András (9th FEB International Scientific Conference: Sustainable Management in the Age of ESG and AI: Navigating Challenges and Opportunities, 2025)
The convergence of artificial intelligence (AI) and blockchain is fostering the emergence of AI-powered cryptocurrencies, which offer sustainable alternatives to energy-intensive digital finance systems. This paper examines how AI supports the environmental, social, and governance (ESG) performance of blockchain ecosystems. AI integration enables the use of energy-efficient consensus mechanisms, improves decentralized finance operations, and facilitates ESG compliance. Projects like Render Network, Fetch.ai, and Ocean Protocol illustrate how AI can increase data processing efficiency, minimize redundant computation, and promote carbon-neutral tokenomics. These platforms support smarter asset distribution through decentralized data marketplaces and machine learning applications. The research methodology involves a review of academic literature, analysis of market statistics, and energy consumption data comparison. The results demonstrate that AI-powered cryptocurrencies can achieve significant energy savings—up to 35% compared to centralized systems—and exhibit strong market growth, with their total capitalization rising more than tenfold between 2021 and 2024. The findings suggest that AI-enhanced blockchain technologies play an essential role in advancing sustainability in digital finance. This study provides guidance for regulators, developers, and investors aiming to align blockchain innovation with green technology principles and responsible market practices.